Refractory contact to a-SiC produced by laser technology methods - Fedorenko, L.L.; Kiseleov, V.S.; Svechnikov, S.V.; Yusupov, M.M.; Beketov, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Developed in the paper are method and technological scheme to obtain ohmic contacts (OC) to a-SiC(:N), Nd - Na ~1 - 3.10¹⁸ cm⁻³ by pulse laser deposition (PLD) of multilayer structures Ni/W/Si₃N₄/W and the following laser annealing (LA). When using an YAG:Nd³⁺ laser, threshold levels and optimal regimes for laser induced diffusion and laser annealing of contacts were determined. It is shown that the Q-switched regime with combined exposure of the fundamental (λ = 1.06 mm) and second (λ = 0.53 mm) harmonics are found as optimal for obtaining minimal contact resistance when YAG:Nd³⁺ laser is used. It is shown that the threshold levels of visual by observed irreversible changes in contact resistance coincide with those of current-voltage characteristics (CVC) and is found to lie in the range area PthCV = = (3 - 8)*10⁷ W*cm⁻² in dependence on thickness of deposited metal layers. The phase transition existence has been established in the process of laser induced modification and annealing on the basis of observed changes in the CVC character and results of surface investigations by Atomic Force Microscopy (AFM). Typical values of resistivity rc of non-fused OC obtained to a-SiC based on Ni/W/Si₃N₄/W structures were close to the value rc ~ (3 ÷ 4)*10⁻⁴W*cm². The contact withstood the current density 104 A*cm⁻² for 100 hours.